Comparative Analysis of Formative And Summative Evaluation in Indonesian Language Learning at SMA Tunas Harapan - Aurel Malinda Zettirah; Fais Afifah; Nur Syamsiyah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to determine the comparison of formative and summative evaluations implemented in schools. This research was conducted using descriptive qualitative methods. The subjects in this research were grade 12 students at Tunas Harapan High School. The data in the research is in the form of student answers in a questionnaire which has been distributed by the author using GForm. The data collection techniques applied in this research are observation techniques and distributing questionnaires. The research results show that in learning Indonesian, Tunas Harapan High School carries out formative evaluations and summative evaluations in the form of questions and final projects. Formative and summative evaluations are interrelated and important in measuring student understanding and helping teachers adjust developments in learning system design.